Rare extracranial localizations of the head and neck schwannomas - Jovanović Milan B.; Čvorović Ljiljana; Poljovka Rastislav; Oroz Aleksandar; Pavićević Ljubomir (Vojnosanitetski Pregled)
Introduction. Schwannomas are tumors of neurogenic origin, that arise from Schwann cells which surround peripheral, cranial and autonomic nerves. Schwannomas account for only 5% of all benign soft tissue tumors, and 25-45% of extracranial schwannomas are present in the head and neck region. They are usually classified according to the nerve of origin and the site within the head and neck. Case report. We presented extremely rare extracranial localizations of schwannomas and discussed about diagnosis and management of these tumors. Conclusion. Schwannomas are slow-growing tumors and late symptoms appearance may cause a delay in diagnosis and treatment of patients with these tumors. An appropriate diagnostic protocol is indispensable tool in performing a differential diagnosis of malignant from benign lesions. Choice of surgical approach depends on schwannomas localization.